Impact of COVID-19 Pandemic on Treatment Management and Clinical Outcome of Aneurysmal Subarachnoid Hemorrhage – A Single-Center Experience - Kashefiolasl, Sepide; Qasem, Lina Elisabeth; Brawanski, Nina; Funke, Moritz; Keil, Fee; Hattingen, Elke; Foerch, Christian; Seifert, Volker; Prinz, Vincent Matthias; Czabanka, Marcus; Konczalla, Juergen (Frontiers in Neurology, 2022)
Background Previous studies reported decreased volumes of acute stroke admissions during the COVID-19 pandemic. We aimed to examine whether aneurysmal subarachnoid hemorrhage (aSAH) volumes demonstrated similar declines in our department. Furthermore, the impact of the pandemic on disease progression should be analyzed. Methods We conducted a retrospective study in the neurosurgical department of the university hospital Frankfurt including patients with the diagnosis of aSAH during the first year of the COVID pandemic. One year cumulative volume for aSAH hospitalization procedures was compared to the year before (03/2020 – 02/2021 vs. 03/2019 – 02/2020) and the last 5 pre-COVID-pandemic years (2015-2020). All relevant patient characteristics concerning family history, disease history, clinical condition at admission, active/past COVID-infection, treatment management, complications, and outcome were analyzed. Results Compared to the 84 hospital admissions during the pre-pandemic years, the number of aSAH hospitalizations (n = 56) declined during the pandemic without reaching significance. No significant difference in the analyzed patient characteristics including clinical condition at onset, treatment, complications, and outcome, between 56 patients with aSAH admitted during the COVID pandemic and the treated patients in the last 5 years in the pre-COVID period were found. In our multivariable analysis, we detected young age (p < 0.05; OR 4.2) and no existence of early hydrocephalus (p < 0.05; OR 0.13) as important factors for a favorable outcome (mRS ≤ 0–2) after aSAH during the COVID pandemic. A past COVID-infection was detected in young patients suffering from aSAH (Age <50years, p < 0.05; OR 10.5) with an increased rate of cerebral vasospasm after aSAH onset (p < 0.05; OR 26). Nevertheless, past COVID-infection did not reach significance as a high-risk factor for unfavorable outcomes. Conclusion There was a relative decrease in the number of patients with aSAH during the COVID-19 pandemic. Despite the extremely different conditions of hospitalization, there was no impairing significant effect on the treatment and outcome of admitted patients with aSAH. A past COVID infection seemed to be an irrelevant limiting factor concerning favorable outcomes.